Derivative Spectrophotometric Determination of Moclobemide in Pharmaceutical Formulations - PATEL, M.B.; PATEL, S.S.; PATEL, G.S. (Asian Journal of Chemistry, 2010)
A first derivative UV spectroscopic method was developed for determination of moclobemide in the tablet dosage form. The first derivative spectrum recorded between 200 and 300 nm and a zero-crossing technique for first derivative measurement at 225 nm was selected. The linear concentration ranges were 2-16 μg/mL, r = 0.9994, n = 5). Between days CV % = 2.8, within day CV % = 2.1, analytical recovery close to 98.37-101.08 % shows the suitability of the method for determination in quality control.